2016
DOI: 10.1108/oir-11-2015-0348
|View full text |Cite
|
Sign up to set email alerts
|

Coherent campaigns? Campaign broadcast and social messaging

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…Norris et al (1999) found considerable difference between the agenda laid out in the party programs before elections and the agenda expressed in press releases during the campaign. Social media have made it even easier to respond directly to new developments during the campaign than press releases (Bode et al, 2011). In sum, the level of control, the semi-public character, and its flexibility offer politicians the possibility of using Facebook strategically to set the campaign agenda. Since issue engagement on Facebook is underexplored, we formulate four research questions to study whether and how these characteristics indeed impact the campaign agenda on Facebook.…”
Section: Facebook Agenda: Controlled Semi-public and Flexiblementioning
confidence: 97%
See 1 more Smart Citation
“…Norris et al (1999) found considerable difference between the agenda laid out in the party programs before elections and the agenda expressed in press releases during the campaign. Social media have made it even easier to respond directly to new developments during the campaign than press releases (Bode et al, 2011). In sum, the level of control, the semi-public character, and its flexibility offer politicians the possibility of using Facebook strategically to set the campaign agenda. Since issue engagement on Facebook is underexplored, we formulate four research questions to study whether and how these characteristics indeed impact the campaign agenda on Facebook.…”
Section: Facebook Agenda: Controlled Semi-public and Flexiblementioning
confidence: 97%
“…Xenos and Foot (2005, p. 183) expect that online campaigning may "alter the dynamic sense in which campaign messages evolve over the course of the election season." Since social media like Facebook are more flexible than other campaign channels, the social media agenda may be more reactive to the public and media agenda (Bode et al 2011). Whenever an issue becomes more salient in the media or for the public in general, political candidates might be triggered to react to this on their Facebook pages.…”
Section: Moving Off Message?mentioning
confidence: 98%
“…A final relevant literature considers the content of political advertising and its determinants. One possibility is that campaigns emphasize a similar message across modes, what Bode et al (2016) call "a single coherent message strategy." Alternatively, campaigns might adapt their message to meet the expectations of the varied audiences across media.…”
Section: What Messages Do Candidates Include In Advertising?mentioning
confidence: 99%
“…Previous studies have shown that different media logics influence the strategic considerations underlying election campaigns (Bode et al, 2016;Kreiss, 2016). On Twitter, most user accounts are publicly visible and accessible even for non-registered audiences.…”
Section: The Use Of Facebook and Twitter By Election Candidatesmentioning
confidence: 99%